38. NUTRITIONAL STATUS, KNOWLEDGE AND PRACTICES OF PREGNANT WOMEN AT THE DEPARTMENT OF OBSTETRICS, HANOI MEDICAL UNIVERSITY HOSPITAL (2023-2024) (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe pregnant women's nutritional status, knowledge and practices visiting the Department of Obstetrics and Gynecology, Hanoi Medical University Hospital in 2023-2024.Subject and method:  A cross-sectional descriptive study from December 2023 to March 2024 on 121 pregnant women visiting the Obstetrics Clinic, Hanoi Medical University Hospital to assess nutritional status, knowledge, and practices on nutrition.Results: According to WHO classification, 80.2% of pregnant women had normal BMI (18.5-24.9 kg/m²), 14.9% of pregnant women had chronic energy deficiency. Upper arm circumference (MUAC) ≥23 cm accounted for 88.4% of pregnant women. According to IOM recommendations, weight gain was 40.2% and 37% gained weight below and 22.8% above the recommendations. 84.3% knew about the amount of food to consume during pregnancy and 80.2% about the appropriate diet. Knowledge about micronutrient supplementation, especially iron (88.4%) and folic acid (87.6%). Multi-micronutrient supplementation was only performed correctly by 62% of pregnant women. Regarding nutritional practices, 55.4% had a higher-than-normal eating level. 61.7% of pregnant women supplemented iron, folic acid and multi-micronutrients during pregnancy, mainly in the first 3 months. The frequency of regular supplementation was 58.1%, 41.9% occasionally supplemented.Conclusions: Pregnant women with unreasonable weight gain during pregnancy account for a high proportion. Most pregnant women who come for check-ups have good knowledge about nutrition during pregnancy. However, the rate of correct nutrition practices during pregnancy is still low. It is necessary to have timely support measures to solve difficulties in changing the awareness and nutritional practices of pregnant women.
Keywords: Nutritional status; knowledge; practice; pregnant women; Hanoi Medical University Hospital